Analysis Of The Alignment Between Vocational High School (SMK) Study Programs And The Competency Needs Of The Workforce Based On Regional Requirements - Riyanto, Sugeng; Mudofir, Mudofir; Rohmadi, Yusup (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to assess the alignment between the study programs offered at Vocational High Schools (SMK) in the Bogor region and the competencies required by the local labor market. Given the rapid development of industries in sectors such as agribusiness, manufacturing, and services in Bogor, ensuring that SMK graduates possess relevant skills is crucial to enhance their employability. This research adopts a mixed-method approach, combining both quantitative and qualitative techniques. The quantitative data, collected through surveys, measures the extent to which study programs meet industry needs, while qualitative data obtained from interviews provide deeper insights into the perceptions of educational stakeholders and industry representatives. The study involves 120 respondents, including school principals, teachers, alumni, and industry representatives. The findings reveal significant gaps in several areas, particularly in technical skills and soft skills such as communication, teamwork, and adaptability, which are essential for readiness in the workforce. Additionally, the lack of collaboration between schools and industries, outdated curricula, and the lack of industry-specific training for educators were identified as key barriers to improving this alignment. The study concludes by recommending the establishment of stronger partnerships between SMK institutions and industries, curriculum updates, and more focused teacher development programs to address the identified gaps and ensure that SMK graduates are better prepared to meet the demands of the local labor market.